Attracting health insurance buyers through selective contracting: Results of a discrete-choice experiment among users of hospital services in the Netherlands - Evelien Bergrath; Milena Pavlova; Wim Groot (Risks, 2014)
In 2006, the Netherlands commenced market based reforms in its health care system. The reforms included selective contracting of health care providers by health insurers. This paper focuses on how health insurers may increase their market share on the health insurance market through selective contracting of health care providers. Selective contracting is studied by eliciting the preferences of health care consumers for attributes of health care services that an insurer could negotiate on behalf of its clients with health care providers. Selective contracting may provide incentives for health care providers to deliver the quality that consumers need and demand. Selective contracting also enables health insurers to steer individual patients towards selected health care providers. We used a stated preference technique known as a discrete choice experiment to collect and analyze the data. Results indicate that consumers care about both costs and quality of care, with healthy consumers placing greater emphasis on costs and consumers with poorer health placing greater emphasis on quality of care. It is possible for an insurer to satisfy both of these criteria by selective contracting health care providers who consequently purchase health care that is both efficient and of good quality.
Keywords: 330; consumer preferences; health insurance; selective contracting; discrete-choice experiment; The Netherlands